Motivation of taekwondo players: An inquiry research among gyms in Belo Horizonte - Pinto, Saulo de Almeida (2016)
This article aims to identify the motivation between men and women to practice taekwondo in Belo Horizonte. The group of respondents, a total of 101 people, being 61 men and 40 women with 17.7 years mean age and 46.5 months mean time of experience, active in this sport at different gyms in this city, has undergone a standard questionnaire, the model of Motivation Inventory to practice sport (Gaya e Cardoso, 1998), whose objective questions, divided into three categories (sports competence, health, friendship and leisure), have three options of answer, each one referring to the level of importance assigned by the respondent to the correspondent question. Similarities were observed in the motivational factors to practice taekwondo between men and women, observing the results of mean and standard deviation (M, SD) for the health category of 2.59±0.56, for the sports competence of 2.40±1,08 , and for friendship and leisure category of 2.13±0.70. It is concluded that health, as a motivational factor, was considered very important by men and women who practice taekwondo, followed by those related to sports competence, while factors related to friendship and leisure showed up less important among the motivational factors analyzed.